Ecosystem Assessment and Fuzzy Systems Management - Cao, Bing-Yuan.; Ma, Sheng-Quan.; Cao, Hu-hua.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
(3z(BEcosystem Assessment and Fuzzy Systems Management(3y (Bis the edited outcome of the 3rd International Conference on Ecosystem Assessment Management (ICEAM) and the Workshop on the Construction of an Early Warning Platform for Eco-tourism (WCEWPE) in Hainan on May 5-12, 2013, Haikou, China. The 3rd ICEAM and the WCEWPE, built on the success of previous conferences, are major Symposiums for scientists, engineers and logistic management researchers presenting their the latest achievements, developments and applications in all areas of Ecosystem Assessment Management, Early Warning Platform for Eco-tourism and fuzziology. It aims to strengthen relations between industry research laboratories and universities, and to create a primary symposium for world scientists. The book, containing 47 papers, is divided into five parts: (3z(BEcosystem Assessment, Management and Information(3y(B; (3z(BIntelligent Algorithm, Fuzzy Optimization and Engineering Application(3y(B; (3z(BSpatial Data Analysis and Intelligent Information Processing(3y(B; (3z(BTourism Culture, Development and Planning(3y (Band (3z(BApplication of Operations Research and Fuzzy Systems(3y(B.s
Ecosystem Assessment, Management and Information -- Intelligent Algorithm, Fuzzy Optimization and Engineering Application -- Spatial Data Analysis and Intelligent Information Processing -- Tourism Culture, Development and Planning -- Application of Operations Research and Fuzzy Systems.
Keywords: Engineering; Operations research; Decision making; Artificial intelligence; Computational intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Operation Research/Decision Theory; Electronic books